What are patient goals after an anterior colporrhaphy operation?. (September 2017) - Kousgaard, Sabrina J.; Bjørk, Jonna; Glavind, Karin
Abstract: Objectives: The aim of this study was to describe patient-reported goals after an anterior colporrhaphy operation for anterior vaginal wall prolapse, the fulfilment of goals, and the correlation with subjective patient-reported outcomes. Study design: A prospective study involving 100 women. Preoperatively, patients completed three modified questions from the International Consultation on Incontinence Questionnaire – Vaginal Symptoms (ICIQ-VS) named ICIQ-VS short form (ICIQ-VS SF) and stated three goals for the operation. A telephone interview was performed 3 months postoperatively. Results: A Visual Analogue Scale (VAS) score from one to 10 estimated the extent to which goals were achieved. Goals were divided into eight groups: 1: mechanical symptoms (bulging), 2: voiding symptoms, 3: quality of life (physical), 4: quality of life (emotional), 5: avoidance of urinary tract infection, 6: cure of incontinence, 7: sexual function and 8: others. ICIQ-VS SF preoperatively was mean 13.6 and postoperatively mean 1.7 (p < 0.001). A total of 276 goals were stated, 63.4% of the goals were fulfilled with a VAS score of 10. The majority of the goals (27%) were in group 1 concerning symptoms of bulging. Mean VAS score for all goals was 8.6 (SD 2.5). Group 1 concerning mechanical symptoms of bulging had most goals fulfilled with a VAS of 10 (76%), and group 6 concerning cure of incontinence had fewest goals fulfilled with a VAS of 10 (31%). Forty patients (40%) fulfilled all their goals. Conclusions: Patient-described goal achievement was high. The majority of the fulfilled goals concerned mechanical symptoms of bulging, and goals concerning incontinence were the least fulfilled.